Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 6 - Section 6.6 - Solving Quadratic Equations by Factoring - Exercise Set - Page 459: 86


$x_{1}=0$ and $x_{2}=1$

Work Step by Step

$(x+6)(x-6)=(2x-9)(x+4)$ $x(x-6)+6(x-6)=2x(x+4)-9(x+4)$ $x^2-6x+6x-36=2x^2+8x-9x-36$ $x^2-36=2x^2-x-36$ $2x^2-x^2-x-36+36=0$ $x^2-x=0$ $x(x-1)=0$ Therefore the solutions are $x_{1}=0$ and $x_{2}=1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.